REVIEW AND ANALYSIS: THE INFLUENCE OF RELATIONSHIP QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION AND ITS IMPLICATIONS ON LOYALTY - Lois frederik; Deden Komar Priatna; Winna Roswina (Dinasti Publisher, 2020)
The purpose of this study is to determine the effect of relationship quality of customer satisfaction, the effect of service quality of customer satisfaction, the influence of relationship quality on customer loyalty, the effect of service quality on customer loyalty, the influence of relationship quality and service quality together on customer satisfaction, the influence relationship quality and service quality together on customer loyalty, the effect of customer satisfaction on loyalty, the effect of relationship quality, service quality, and customer satisfaction together on student loyalty in informatics in Bandung. The research method used is descriptive verification analysis research using Structural Equation Modeling (SEM) analysis design. From the results of this study, it can be concluded that the quality of service and service quality both partially and simultaneously will affect customer satisfaction resulting in increased customer loyalty.